Resection of symptomatic focal nodular hyperplasia of the liver with pre-operative angioembolization - Othmane Alaoui; Abdelhalim Mahmoudi; Khalid Khattala; Youssef Bouabdallah (Elsevier, 2022)
Focal nodular hyperplasia (FNH) is a rare benign liver tumor in children. Treatment is only mandatory if the tumor is symptomatic and/or large. Transarterial embolization offers a safe alternative to surgery, but above all the possibility of performing limited hepatectomies. We report 2 cases, of 10 years old girl and 11 years old boy, who have a focal nodular hyperplasia affecting the left liver for the first one and the right liver for the second one. They were managed successfully by preoperative transarterial embolization followed by surgery.